Mustaqillik arafasida O`zbekistonda turizm sohasining holati - Isoyeva Ismigul, Murodov Halim (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2023)
The article analyzes the fact that before independence, tourism in Uzbekistan did not function independently as a socio-economic organization, problems and shortcomings in tourism and their causes, as well as positive changes in the field of tourism.